2020
DOI: 10.1097/md.0000000000019841
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study for external washing by traditional Chinese medicine in the treatment of multiple infectious wounds of diabetic foot

Abstract: Background: Diabetic foot (DF) is among the most serious complications of type 2 diabetes. DF infection (DFI) is a key factor in the deterioration and development of DF, so controlling infection plays an important role in the treatment of the disease. Traditional Chinese medicine foot bath has been widely used in China as a complementary and alternative therapy to improve circulation and infection control of DF. However, the existing evidence shows that its efficacy and safety are still insufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…TCM foot bath using decoctions increases blood circulation for Grade 0 DF[ 68 ]. Additionally, herbal foot baths can improve local microcirculation and regulate skin permeability to increase drug absorption, thus effectively increasing drug concentration[ 69 , 70 ].…”
Section: Foot Bathmentioning
confidence: 99%
See 1 more Smart Citation
“…TCM foot bath using decoctions increases blood circulation for Grade 0 DF[ 68 ]. Additionally, herbal foot baths can improve local microcirculation and regulate skin permeability to increase drug absorption, thus effectively increasing drug concentration[ 69 , 70 ].…”
Section: Foot Bathmentioning
confidence: 99%
“…Additionally, herbal foot baths can improve local microcirculation and regulate skin permeability to increase drug absorption, thus effectively increasing drug concentration[ 69 , 70 ]. Recently, clinical trials have been designed to examine the efficacy and safety of TCM foot baths[ 68 , 71 ]. Nevertheless, foot baths can spread infection at the ulcer site in patients with chronic limb ulcers and increase the rate of toe loss (53%) and major amputation (30%)[ 72 ].…”
Section: Foot Bathmentioning
confidence: 99%
“…Previous study found that a group of traditional Chinese medicine (TCM) ( e.g. , herbal medicine foot bath decoction[ 5 ], TCM injections[ 6 , 7 ], Chinese herbal medicine ulcer oil[ 8 ], moxibustion[ 9 ], Astragali Radix and Rehmanniae Radix Mixture[ 10 ], the peptide compounds of Wuguchong[ 11 ], Astragali Radix and Rehmanniae Radix[ 12 , 13 ]) played an important role in the treatment of the disease. Some study also found that interventional radiology plays a crucial role in the treatment of diabetic foot disease[ 14 ].…”
Section: To the Editormentioning
confidence: 99%
“…In recent years, most diabetic foot patients in China are adopting TCM and western medicine[ 5 , 15 ]. A series of systematic review articles showed that TCM can increase the clinical effective rate of conventional therapies by 27%[ 6 ], regulate the signaling pathways to promote diabetic wound healing[ 16 ].…”
Section: To the Editormentioning
confidence: 99%
“…Many traditional Chinese medicine (TCM) ointments effectively treat diabetic ulcers, and they show a more significant curative effect during the early stages of treatment than in the later stages [ 3 ]. However, most Chinese herbal preparations for external application show intended results only after the correct differentiation of TCM syndrome.…”
Section: Introductionmentioning
confidence: 99%